Peningkatan Minat Baca Anak Melalui Takra Posa (Taman Literasi Pojok Sawah) di Desa Miru, Sekaran, Lamongan - Walidatul Amiyah; Aan Afit Andriansyah (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2025)
The low literacy rate in rural areas of Indonesia remains a significant challenge in improving the quality of human resources. This study aims to enhance children's reading interest through the Takra Posa (Taman Aksara Pojok Sawah) program in Miru Village, Sekaran District, Lamongan Regency, using a participatory approach rooted in local wisdom. This research employs a qualitative method with observation, interviews, and documentation as data collection techniques. The program was implemented in several stages: needs assessment, resource provision, literacy activities, training, and evaluation. The results show a significant increase in children's interest in reading; the number of children who enjoy reading rose from 10 to 55. Activities such as group reading, storytelling, creative competitions, and outdoor reading created a fun and engaging learning environment. This program also had a positive impact on parental and community involvement, fostering a collective awareness of the importance of literacy. Therefore, Takra Posa can serve as an effective model for nature-based, community-driven reading spaces in rural areas.